Expression of the P/Q (Cav2.1) calcium channel in nodose sensory neurons and arterial baroreceptors - Tatalovic, Milos (2012)
The predominant calcium current in nodose sensory neurons, including the subpopulation of baroreceptor neurons, is the N-type channel, Cav2.2. It is also the primary calcium channel responsible for transmitter release at their presynaptic terminals in the nucleus of the solitary tract in the brainstem. The P/Q channel, Cav2.1, the other major calcium channel responsible for transmitter release at mammalian synapses, represents only 15–20% of total calcium current in the general population of sensory neurons and makes a minor contribution to transmitter release at the presynaptic terminal. In the present study we identified a subpopulation of the largest nodose neurons (capacitance > 50pF) in which, surprisingly, Cav2.1 represents over 50% of the total calcium current, differing from the remainder of the population. Consistent with these electrophysiological data, anti-Cav2.1 antibody labeling was more membrane delimited in a subgroup of the large neurons in slices of nodose ganglia. Data reported in other synapses in the central nervous system assign different roles in synaptic information transfer to the P/Q-type versus N-type calcium channels. The study raises the possibility that the P/Q channel which has been associated with high fidelity transmission at other central synapses serves a similar function in this group of large myelinated sensory afferents, including arterial baroreceptors where a high frequency regular discharge pattern signals the pressure pulse. This contrasts to the irregular lower frequency discharge of the unmyelinated fibers that make up the majority of the sensory population and that utilize the N-type channel in synaptic transmission.